North, East, South, West: Georgia Russell's Scottish Cut-out Landscapes - Béchard-Léauté, Anne (Sens public)

(untitled) (Département des littératures de langue française, 2021)
The work of Scottish sculptor Georgia Russell presents the viewer with unidentified objects, unknown hybrids created out of a process of laceration with a scalpel. The books or photographs that she dissects unfurl outwards into sculptural objects that operate in space in an organic manner, be they totemic figures or paper landscapes. The common denominator of this body of works is the automatic technique of cutting out, making incisions with the scalpel being the equivalent of making marks with a pencil for the artist. This act, which marries gesture and rhythm, space and time, has become the foundation of Georgia Russell's oeuvre and oscillates between the flat surface of the printed page and the volume of the sculptural object. This paper addresses the seemingly straightforward significance of Russell's cut-out landscapes. Once they have been sliced and transformed into lacework, her cut-out landscapes are not just a support for retrieval but have a deeper, nostalgic meaning. The different media Russell chooses to work with are addressed as well as their original content. The link between Russell's work and literature is introduced in order to study the visual allusions she makes to the Scottish landscape while working from her French studio.